ANALISIS POLA SUHI (SURFACE URBAN HEAT ISLAND) KOTA PESISIR (COASTAL CITY) WILAYAH PANTAI UTARA JAWA MENGGUNAKAN DATA SENTINEL-3 SLSTR MULTITEMPORAL (Studi Kasus : Kabupaten Kendal dan Kabupaten Cirebon) - Moh Adib Yahya Al Hakim; Bandi Sasmito; Firman Hadi (Jurnal Geodesi UNDIP, 2022)
The development of a country continues to be followed by high population growth affecting environmental characteristics in coastal areas, especially by human activities and uncertain climatic conditions that can form the Surface Urban Heat Island (SUHI) phenomenon. The purpose of the study was to obtain a map of the distribution of SUHI intensity in 2019, 2020, and 2021 in Cirebon and Kendal regencies to determine the pattern and consistency of SUHI intensity. One of the impact distributions of SUHI intensity can be identified by the Urban Thermal Field Variance Index (UTFVI), where consistency is also seen using the Getis-Ord Gi hot-spot and cold-spot statistics. The UTFVI value is based on the urban area of SAR Sentinel-1A and LST Sentinel-3 SLSTR Level-2 with RMSE 5,419 oC which is moderately correlated with the LST of the BMKG station in 2021. The pattern of distribution of SUHI intensity in coastal areas consistently shows that the area with the largest area is the area not affected by SUHI and the area affected by SUHI is the strongest. The pattern not always leading to the coastal area but in the Cirebon Area leading to Cirebon City and in the southern part of the Kendal Area leading to toll road rest areas and industrial areas.